Proton Pump Inhibitor Use Affects Pseudarthrosis Rates and Influences Patient-Reported Outcomes. Issue 1 (February 2020) - Mangan, John J.; Divi, Srikanth N.; McKenzie, James C.; Stull, Justin D.; Conaway, William; Casper, David S.; Goyal, Dhruv K. C.; Nicholson, Kristen J.; Galetta, Matthew S.; Wagner, Scott C.; Kaye, I. David; Kurd, Mark F.; et al.
Study Design: Retrospective cohort review Objectives: Cervical pseudarthrosis is a frequent cause of need for revision anterior cervical discectomy and fusion (ACDF) and may lead to worse patient-reported outcomes. The effect of proton pump inhibitors on cervical fusion rates are unknown. The purpose of this study was to determine if patients taking PPIs have higher rates of nonunion after ACDF. Methods: A retrospective cohort review was performed to compare patients who were taking PPIs preoperatively with those not taking PPIs prior to ACDF. Patients younger than 18 years of age, those with less than 1-year follow-up, and those undergoing surgery for trauma, tumor, infection, or revision were excluded. The rates of clinically diagnosed pseudarthrosis and radiographic pseudarthrosis were compared between PPI groups. Patient outcomes, pseudarthrosis rates, and revision rates were compared between PPI groups using either multiple linear or logistic regression analysis, controlling for demographic and operative variables. Results: Out of 264 patients, 58 patients were in the PPI group and 206 were in the non-PPI group. A total of 23 (8.71%) patients were clinically diagnosed with pseudarthrosis with a significant difference between PPI and non-PPI groups ( P = .009). Using multiple linear regression, PPI use was not found to significantly affect any patient-reported outcome measure. However, based on logistic regression, PPI use was found to increase the odds of clinically diagnosed pseudarthrosis (odds ratio 3.552, P = .014). Additionally, clinically diagnosed pseudarthrosis negatively influenced improvement in PCS-12 scores ( P = .022). Conclusions: PPI use was found to be a significant predictor of clinically diagnosed pseudarthrosis following ACDF surgery. Furthermore, clinically diagnosed pseudarthrosis negatively influenced improvement in PCS-12 scores.